2009
DOI: 10.1681/asn.2008060579
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Is Associated with Mortality in Chronic Hemodialysis Patients

Abstract: Recent studies have associated rosiglitazone, a thiazolidinedione drug, with adverse cardiovascular outcomes in the general population with diabetes. Using data from the Dialysis Outcomes and Practice Patterns Study in the United States, we examined cardiovascular hospitalization and mortality associated with prescription of rosiglitazone, compared with other oral hypoglycemic agents, among 2393 long-term hemodialysis patients who were followed for a median of 1.1 yr. We assessed mortality risk using Cox model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 32 publications
1
45
0
1
Order By: Relevance
“…Also in case of these outcome variables, IV analysis has been applied with two-stage method. In that case, the second-stage model could be a Cox proportional hazards model [78][79][80]. However, Brookhart et al [3] stated that this approach for IV analysis is not motivated by a theoretical model and, therefore, parameters that are obtained from this approach may not be causally interpretable.…”
Section: Other Estimation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in case of these outcome variables, IV analysis has been applied with two-stage method. In that case, the second-stage model could be a Cox proportional hazards model [78][79][80]. However, Brookhart et al [3] stated that this approach for IV analysis is not motivated by a theoretical model and, therefore, parameters that are obtained from this approach may not be causally interpretable.…”
Section: Other Estimation Methodsmentioning
confidence: 99%
“…However, Brookhart et al [3] stated that this approach for IV analysis is not motivated by a theoretical model and, therefore, parameters that are obtained from this approach may not be causally interpretable. Examples of this approach are a study of the effect of rosiglitazone on (time to) cardiovascular hospitalization and all-cause mortality using facility-prescribing patterns as an IV [78], and a study of the effect of adjuvant chemotherapy on (time to) breast cancer recurrence using physician preference as an IV [79].…”
Section: Other Estimation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiazoledinedione use has reduced nowadays with reports of cardiovascular mortality with rosiglitazone (14) and possibly bladder carcinoma with pioglitazone, although the latter is an unproven association (15). Both these drugs do not accumulate in patients with CKD, but they can cause edema and heart failure (16).…”
Section: Oral Antidiabetic Agents In Ckd (Table 1)mentioning
confidence: 99%
“…Table 3 summarizes the mechanisms of action and potential advantages and disadvantages of different classes of oral agents. It is noteworthy that the results of the Dialysis Outcomes and Practice Patterns Study (DOPPS) demonstrated that in long-term hemodialysis patients rosiglitazone was associated with a significantly higher all-cause (hazard ration 1.59) and cardiovascular mortality and a 3.5 fold increase of hospitalizations due to myocardial infarction (Ramirez et al, 2009). In contrast to the DOPPS study results, in an analysis of the national cohort study consisting of more than 5,000 dialysis patients with type 2 diabetes Brunelli et al observed a lower incidence of all-cause mortality in patients not on insulin vs. insulin requiring diabetic patients (Brunelli et al, 2009).…”
Section: Pharmacological Managementmentioning
confidence: 99%